Sosialisasi Gizi Guna Meningkatkan Pengetahuan dan Kesadaran Siswa Sekolah Dasar Wonosuko 2 Mengenai Pola Hidup Bersih dan Sehat - Wardhono, Adhitya; Qori’ah, Ciplis Gema; Puspito, Agung Nugroho; Ubaidillah, Mohammad; Avivi, Sholeh; Anggira, Desi; Imelda, Laela Vita; Intansari, Herlindha Angghelinna Devfi; Hartita, Margaretha Putri; Aurelya, Lalyta; Cahyani, Ardhya Pramisti Regita; Nasir, M Abd (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Primary schools have an important role in development, therefore the health of primary school children needs to be maintained properly. Based on data from 2000 the prevalence of stomach worms in elementary school children is 60-80% in 250,000 public and private schools and every year 100,000 Indonesian children die from diarrhea (Dep.Kes.RI, 2007). This activity method is in the form of lectures and technical assistance to increase the knowledge and awareness of elementary school students precisely at SD Negeri Wonosuko 2 located in Wonosuko Village, Wonosuko District, Bondowoso Regency. The material provided regarding healthy living behavior by applying Balanced Nutrition guidelines includes The results obtained in the